제오카본을 이용한 암모니아성 질소와 질산성 질소 동시 제거에 관한 기초 연구 - 김서아(Seo A Kim); 홍지숙(Ji Sook Hong); 서정권(Jeong Kwon Suh); 강호(Ho Kang); 이정민(Jung Min Lee) (Daehan hwan'gyeong gonghag hoeji, 2005)
The objective of this study is to investigate the possibility for water treatment, and to evaluate the efficiency of simultaneous removal of ammonium and nitrate by the surface modified zeocarbon. The surface modification was done by acid treatment using HCl. As a result of modification, strength of the modified zeocarbon was enhanced about 62% higher than that of in original one. This indicates that the modified zeocarbon was suitable for the application of water treatment. In the removal experiments of ammonium and nitrate, the removal efficiency showed about two times higher in the modified zeocarbon and the dependences of pH and temperature were found to be minimized. This indicates that the modified zeocarbon was effective for simultaneous removal of ammonium and nitrate from aqueous solution. Consequently, our results could be used as basic data to design of one-stage ammonium/nitrate simultaneous removal system. 본 연구에서는 기상용 제오카본을 수처리에 적합하도록 염산으로 표면 개질 하였으며, 개질된 제오카본을 이용하여 단일 공정을 통한 암모니아성 질소와 질산성 질소 동시 제거 가능성을 평가하고자 하였다. 제오카본과 비교하여 표면 개질 제오카본의 강도가 62% 정도 증가하였으며, 암모니아성 질소와 질산성 질소 및 총질소 제거율이 약 2배 증가하였다. 또한 암모니아성 질소와 질산성 질소 제거 효율은 pH 및 온도 변화에 거의 영향을 받지 않았다. 따라서 수중에 존재하는 암모니아성 질소와 질산성 질소의 동시 제거가 매우 효과적으로 이루어질 수 있었으며, 본 연구 결과를 토대로 암모니아성 질소와 질산성 질소를 동시 제거할 수 있는 단일 공정 설계를 위한 기본 데이터 제시가 가능하였다.